Metagenomics Reveals Dysbiosis and a Potentially Pathogenic N. flavescens Strain in Duodenum of Adult Celiac Patients. (June 2016) - D'Argenio, Valeria; Casaburi, Giorgio; Precone, Vincenza; Pagliuca, Chiara; Colicchio, Roberta; Sarnataro, Daniela; Discepolo, Valentina; Kim, Sangman M; Russo, Ilaria; Del Vecchio Blanco, Giovanna; Horner, David S; Chiara, Matteo; et al.
Abstract : OBJECTIVES: Celiac disease (CD)‐associated duodenal dysbiosis has not yet been clearly defined, and the mechanisms by which CD‐associated dysbiosis could concur to CD development or exacerbation are unknown. In this study, we analyzed the duodenal microbiome of CD patients. METHODS: The microbiome was evaluated in duodenal biopsy samples of 20 adult patients with active CD, 6 CD patients on a gluten‐free diet, and 15 controls by DNA sequencing of 16S ribosomal RNA libraries. Bacterial species were cultured, isolated and identified by mass spectrometry. Isolated bacterial species were used to infect CaCo‐2 cells, and to stimulate normal duodenal explants and cultured human and murine dendritic cells (DCs). Inflammatory markers and cytokines were evaluated by immunofluorescence and ELISA, respectively. RESULTS: Proteobacteria was the most abundant and Firmicutes and Actinobacteria the least abundant phyla in the microbiome profiles of active CD patients. Members of the Neisseria genus (Betaproteobacteria class) were significantly more abundant in active CD patients than in the other two groups ( P =0.03). Neisseria flavescens (CD ‐ Nf ) was the most abundant Neisseria species in active CD duodenum. Whole‐genome sequencing of CD ‐ Nf and control ‐ Nf showed genetic diversity of the iron acquisition systems and of some hemoglobin‐related genes. CD ‐ Nf was able to escape the lysosomal compartment in CaCo‐2 cells and to induce an inflammatory response in DCs and in ex‐vivo mucosal explants. CONCLUSIONS: Marked dysbiosis and an abundance of a peculiar CD ‐ Nf strain characterize the duodenal microbiome in active CD patients thus suggesting that the CD‐associated microbiota could contribute to the many inflammatory signals in this disorder.